PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - R Radiman (Faculty of Economics and Business, Universitas Warmadewa, 2019)
This research aims to test and analyze the effect of the influence of corporate social responsibility (CSR) on financial performance in mining companies listed on the Indonesia Stock Exchange (IDX). In addition, this research aims is to determine how much the contribution of the independent variable Corporate Social Responsibility affects the dependent variable Return On Asset and Return On Equity. The population in this research is a mining company listed on the Indonesia Stock Exchange, which amounts to 41 companies. sampling in this research using purposive sampling technique, so that the sample obtained amounted to 10 companies. This type of research is quantitative and the data analysis technique used is multiple linear regression which was previously tested with the classic assumption test. Then testing the hypothesis, namely the t test and testing the coefficient of testing. The data analysis technique is assisted by using SPSS version 16 for windows. The results showed that partially Corporate Social Responsibility did not significantly influence Return On Assets and Corporate Social Responsibility did not significantly influence Return On Equity. The coefficient of determination (Rç°¡) is 0.009, in this case the contribution of the variable Corporate Social Responsibility that affects Return On Assets and Return On Equity in Mining companies listed on the Indonesia Stock Exchange is 7% while the remaining 93% is influenced by other variables not examined in this research.